Role of some Hematological and Immunological Parameters in Pathogenesis of Ankylosing Spondylitis in a Sample of Iraqi Male Patients. - Sumyah H. Hassan; Ekhlass N. Ali; Ibtesam G. Auda; Mohammed Hadi Munshed Al-Osami (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Ankylosing spondylitis (AS) is an autoimmune disease that is chronic, systemic seronegative inflammatory spondyloarthropathy. Magnetic resonance imaging (MRI) was used in the diagnosis of AS patients, as well as other clinical and laboratory criteria like symptoms and elevated levels of ESR and C-reactive protein. The current study intends to establish the role of certain hematological and immunological factors in the development of AS and to analyze the connections between these indicators. The methods of work included blood sample collection from 100 participants (50 AS male patients and 50 healthy controls). The ages of both groups were between 20-60 years. Two milliliters of blood were used for CBC (Hb and WBC) and ESR analysis, while three milliliters of the blood were put in a gel tube to measure serum levels of CRP, IL-17, and IL-22 using the ELISA technique. It shows that the AS was most prevalent in the age range of 20-35 years (p = 0.013). There was a highly significant increase (p<0.001) in, ESR, CRP, IL17, and IL22 in AS patients as a result of inflammation compared to controls, while the Hb is significantly raised in the control group as compared with patients and except for the WBC level that was non-significant. The WBC was a non-specific parameter associated with AS development, while AS patients have lower Hb and increased levels of CRP, ESR, IL17, and IL22 that were excellent biomarkers for the diagnosis of AS they were all greater in AS patients than in healthy controls, and they might be recommended as a predictive measure for AS patients.